2019
DOI: 10.3390/hydrology6020056
|View full text |Cite
|
Sign up to set email alerts
|

An Urban Flash Flood Alert Tool for Megacities—Application for Manhattan, New York City, USA

Abstract: Urban flooding is a frequent problem affecting cities all over the world. The problem is more significant now that the climate is changing and urbanization trends are increasing. Various, physical hydrological models such as the Environmental Protection Agency Storm Water Management Model (EPA SWMM), MIKE URBAN-II and others, have been developed to simulate flooding events in cities. However, they require high accuracy mapping and a simulation of the underground storm drainage system. Sadly, this capability is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This study uses GIS and NYC's digital elevation model (DEM) (1 m resolution) to create 889 sub-basins for NYC. The study conducted by Al-Suhili et al showed that increasing the number of sub-basins in an urbanized area can improve the accuracy of flood inundation [32]. This study also adopted this method and completed the division of sub-basins through GIS.…”
Section: Creating a Sub-basin Databasementioning
confidence: 97%
“…This study uses GIS and NYC's digital elevation model (DEM) (1 m resolution) to create 889 sub-basins for NYC. The study conducted by Al-Suhili et al showed that increasing the number of sub-basins in an urbanized area can improve the accuracy of flood inundation [32]. This study also adopted this method and completed the division of sub-basins through GIS.…”
Section: Creating a Sub-basin Databasementioning
confidence: 97%
“…For islands like Jamaica, where steep topography abides the production of heavy rainfall, large amounts of precipitation occur over high elevations that increase as wind speed increases [17]. Furthermore, it is expected that global climate change will impact regional precipitation patterns and thus influence the recurrence of associated risks [21][22][23]. Moreover, due to limited natural and human resources, topography, population size, and economy, small Caribbean islands like Jamaica have been identified as most vulnerable to climate change and extremes [15,24].…”
Section: Flooding Hazardsmentioning
confidence: 99%
“…In the last decades, large efforts have been focused on the modelling of urban floods, with different aims such as hazard mapping, risk communication, probabilistic approaches, design and management of green/grey risk mitigation and climate adaptation solutions (Al-Suhili et al, 2019;Bates et al, 2010;Costabile, Costanzo, De Lorenzo, et al, 2021;Di Baldassarre et al, 2010;Hammond et al, 2015;Nguyen et al, 2006). Many approaches and models exist that are able to tackle those goals with different degrees of detail, ranging from empirical/conceptual black-box models (e.g., Chen et al, 2009;Samela et al, 2020) to rigorous approaches solving mono-, two-or threedimensional problems (Bulti & Abebe, 2020;Costabile, Costanzo, De Lorenzo, & Macchione, 2020;Di Baldassarre et al, 2010;Henonin et al, 2013;Martins et al, 2017;Martins et al, 2018;Taskinen & Bruen, 2007).…”
Section: Simplifying Assumptions For Scenario Analysis and Data Unavailability Issuesmentioning
confidence: 99%